THE CONSTITUENT ELEMENTS AND THE NEED FOR STATE REGULATION OF SMALL BUSINESS AND PRIVATE ENTREPRENEURSHIP - Abdieva, Nilufar; Abdullayeva , Rano; Rajabov, Utkir (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Abstract. The article analyzes the importance of small business and private entrepreneurship in the sustainable development of the country's economy and in meeting the endlessly growing needs of the population. the need for state regulation and conditions for guaranteeing private property and creating an attractive investment environment are analyzed.